Long-Term Effects from Early Exposure to Research: Evidence from the NIH "Yellow Berets" - Azoulay, Pierre; Greenblatt, Wesley; Heggeness, Misty L (International Journal of Population Data Science, 2018)
In the late 1960s, the federal government was looking for young, healthy men to enlist in the military to help ensure success in the Vietnam War. Not enough men were voluntarily choosing to enlist. In 1969, the federal government implemented a lottery draft. Recruiters traveled the U.S. encouraging enlistment and explaining the draft requirements. They made visits to medical schools explaining options to newly minted MDs. Those options included: (1) be drafted and (possibly) go to war or (2) enlist in the Public Health Service (PHS) using the skills learned in their medical profession in the U.S. The PHS included an option to travel to Bethesda, Maryland and enlist as a Training Associate (TA) at the National Institutes of Health (NIH) to work in one of the scientific intramural labs on campus and receive training by some of the top medical research scientists in the nation. For this study, we searched the National Archives for the physical paper applications of those individuals who applied to the NIH Intramural Training Associates program before, during, and after the lottery draft. We digitalized their applications, combed public documents in search of up-to-date career information, and linked them to their publications and patents to-date. We created a rich linked dataset of administrative records from which we examine the impact of early career, high intensity research training on the probability of staying in research and the overall impact on advancing science. This paper describes our results evaluating the impact of this federal program.